Determinación de zonas urbanas vulnerables a inundaciones de la quebrada de Cunduana mediante el uso de modelos hidrológicos e hidráulicos - Jácome Pérez, Mirian Verónica (2022)
Floods are becoming more common globally, due to lack of planning and productive development near riverbeds. Hydrological studies are essential to obtain maximum flood flows through applications of rain-runoff principles, while the implementation of a hydraulic model helps to obtain flood surfaces reflecting depths and velocities to identify areas at risk. This study focused on obtaining urban areas which are susceptible to flooding in Riobamba, based on the physiographic, geomorphological and drainage system parameters of the Cunduana Ravine Basin, or Cuenca Quebrada de Cunduana (in Spanish); for determining the Curve Number (CN) and implement a rain-runoff model that allows estimating maximum flood flows. Subsequently, using one-dimensional, and two-dimensional hydraulic modeling it was possible to obtain flood maps, which were contrasted with information obtained from local newspapers and interviews to experts. The results showed that the affected areas in return periods of fifty years may be broader than the ones registered on March 2,2021. Causing an increase in submerged urban areas and high flow velocities, which could generate erosion of surfaces, sediment drag, and even dragging of large objects.